2001
DOI: 10.1177/003435520104400407
|View full text |Cite
|
Sign up to set email alerts
|

Test Review: Woodcock, R. W., McGrew, K. S., & Mather, N. (2001). Woodcock-Johnson® III Test. Riverside Publishing Company. Itasca, IL

Abstract: The Woodcock-Johnson® III (WJ III) is an individually administered battery of tests that provide a comprehensive measure of abilities and achievement across a wide age range. This battery of tests represents the most recent revision of the original Woodcock-Johnson Psycho-Educational Battery (WJ) published in 1977. The WJ III consists of two distinct, co-normed batteries: the WJ III Tests of Cognitive Abilities (WJ III COG) and the WJ III Tests of Achievement (WJ III ACH), Forms A and B. This co-norming pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…Split-half reliability has been reported as .80 (Dunn & Dunn, 1981), and scores on the PPVT-Rand PPVT-III have shown good concurrent (Hodapp & Gerken, 1999; Zucker & Riordan, 1988) and predictive (Zucker & Riordan, 1990) validity, including among diverse populations of children (Campbell, Bell, & Keith, 2001; Washington & Craig, 1999). Second, children completed three of the subtests of the Woodcock-Johnson III Tests of Achievement (WJ-III; Woodcock, McGrew, & Mather, 2001) targeting language development (Letter-Word Identification and Sound Awareness) and math development (Applied Problems). Both the reliability and validity of the WJ-III are adequate (Woodcock et al, 2001), and construct validity has been demonstrated for diverse groups of children (Edwards & Oakland, 2006).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Split-half reliability has been reported as .80 (Dunn & Dunn, 1981), and scores on the PPVT-Rand PPVT-III have shown good concurrent (Hodapp & Gerken, 1999; Zucker & Riordan, 1988) and predictive (Zucker & Riordan, 1990) validity, including among diverse populations of children (Campbell, Bell, & Keith, 2001; Washington & Craig, 1999). Second, children completed three of the subtests of the Woodcock-Johnson III Tests of Achievement (WJ-III; Woodcock, McGrew, & Mather, 2001) targeting language development (Letter-Word Identification and Sound Awareness) and math development (Applied Problems). Both the reliability and validity of the WJ-III are adequate (Woodcock et al, 2001), and construct validity has been demonstrated for diverse groups of children (Edwards & Oakland, 2006).…”
Section: Methodsmentioning
confidence: 99%
“…Second, children completed three of the subtests of the Woodcock-Johnson III Tests of Achievement (WJ-III; Woodcock, McGrew, & Mather, 2001) targeting language development (Letter-Word Identification and Sound Awareness) and math development (Applied Problems). Both the reliability and validity of the WJ-III are adequate (Woodcock et al, 2001), and construct validity has been demonstrated for diverse groups of children (Edwards & Oakland, 2006). Finally, children were administered the Story and Print Concepts (SPC; Administration on Children, Youth, and Families [ACYF], 2003), which measures book and print knowledge as well as story comprehension.…”
Section: Methodsmentioning
confidence: 99%
“…All participants (including Controls) completed four proficiency measures: (a) a written self-report measure where they were asked to rate their proficiency level on a scale from 1 to 7 in listening comprehension, reading comprehension, pronunciation, fluency, vocabulary, and grammatical ability; (b) a written C-test (Italian version: Kra s, 2008), where they were asked to fill in the blanks in five short texts in which twenty words in each text had been partially deleted; (c) a written error-detection test designed specifically for this study, where participants had to detect and correct a number of errors in two separate texts; and lastly, (d) a timed verbal semantic fluency task where participants were asked to produce as many vocabulary items from two categories ("animals" and "fruits and vegetables") as possible within 1 min. Participants also completed (a) a timed reading fluency task where they had to silently read and answer as many true-false statements as possible in 3 min (Woodcock, McGrew, Mather, & Schrank, 2003; adapted into Italian for this study); and (b) the letter-number-sequencing task from the Italian WAIS-IV as a measure of working memory (Orsini & Pezzuti, 2013). The purpose of these tasks was to ensure that group differences were not due to differences in reading speed and/or working memory capacity, given the rapid-serial-visual presentation mode of the sentence stimuli during the ERP experiment.…”
Section: Behavioral Measuresmentioning
confidence: 99%
“…Both groups completed four proficiency measures : (1) A written self-report measure where they rated their L1 proficiency level on a scale from 1 to 7 in listening, reading, pronunciation, fluency, vocabulary, and grammatical ability; (2) A written C -test (Italian version: Kraš, 2008), where they were asked to fill in the blanks in 5 short texts in which 20 words in each text had been partially deleted; (3) A written error-detection test (Kasparian, 2015), where they had to detect and correct errors in two texts; and (4) A timed verbal semantic fluency task where they were asked to produce as many vocabulary items a given semantic category within 1 min. They also completed (1) a timed reading fluency task where they silently read and answered as many true-false statements as possible in 3 min (adapted into Italian based on Woodcock et al, 2003), and (2) the letter-number-sequencing task from the Italian WAIS-IV as a measure of WM (Orsini and Pezzuti, 2013). The purpose of these tasks was to ensure that any group differences were not a result of reading speed and/or WM differences.…”
Section: Methodsmentioning
confidence: 99%